2018
DOI: 10.5194/isprs-archives-xlii-5-829-2018
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Invasive Aquatic Macrophytes Over Tapi River

Abstract: <p><strong>Abstract.</strong> Aquatic macrophytes are important elements of freshwater ecosystems, fulfilling a pivotal role in the ecological functions of these environments and biogeochemical cycles. Although aquatic macrophytes are beneficial, some species can hinder human activity. They can clog reservoirs and reduce water availability for human needs. Surveys of macrophytes are hindered by logistic problems, and remote sensing represents a powerful alternative, allowing comprehensive ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…In this latter more applied paper category a total of 40 articles were found, and the majority of them were related to lakes (85% of the applied articles). In addition, imaging spectroscopy has been also attracting a wide interest [28] and reference therein since its simultaneous collection of narrower and contiguous bands is improving aquatic ecosys-tem mapping for the retrieval of parameters describing water quality, aquatic vegetation (e.g., biomass [41], invasive species identification [42]) and benthic substrates that might be undetectable with broadband multispectral sensors [15,27,40,[43][44][45][46][47][48]. In such a context, airborne data (e.g., APEX, AISA, MIVIS) have been providing unique data at high spectral and spatial resolution for performing advanced mapping as well to support satellite mission development and verification (e.g., [49][50][51][52]).…”
Section: Introductionmentioning
confidence: 99%
“…In this latter more applied paper category a total of 40 articles were found, and the majority of them were related to lakes (85% of the applied articles). In addition, imaging spectroscopy has been also attracting a wide interest [28] and reference therein since its simultaneous collection of narrower and contiguous bands is improving aquatic ecosys-tem mapping for the retrieval of parameters describing water quality, aquatic vegetation (e.g., biomass [41], invasive species identification [42]) and benthic substrates that might be undetectable with broadband multispectral sensors [15,27,40,[43][44][45][46][47][48]. In such a context, airborne data (e.g., APEX, AISA, MIVIS) have been providing unique data at high spectral and spatial resolution for performing advanced mapping as well to support satellite mission development and verification (e.g., [49][50][51][52]).…”
Section: Introductionmentioning
confidence: 99%
“…The reviews reported in [23,24] highlighted the significant increase in remote sensing studies of inland water quality, due both to improved access to Earth Observation (EO) data and increasing computational capabilities. Particularly, imaging spectroscopy has gained wide interest [25][26][27][28], as the collection of data in narrower, contiguous bands is improving aquatic ecosystem mapping for the simultaneous retrieval of parameters describing water quality and aquatic vegetation (e.g., biomass [29] and the identification of invasive species [30]). In the last few years, hyperspectral spaceborne and airborne images have been providing significant advances in algorithm development and innovative mapping tools [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…24 Its excessive growth causes various environmental (including ecological and socioeconomic) impacts that are hazardous to aquatic systems and disable human uses of surface waters. 25 It causes hypoxia, threatens freshwater quality and availability, 3,8,[26][27][28][29] worsens the quality of freshwater ecosystems, 30 including the quality of the aquatic life, 8,31,32 by causing changes in macroinvertebrate species richness 33 and biodiversity loss, 20,34,35 and promotes breeding grounds for pests and vectors. 36,37 Moreover, the expansion of water hyacinth obstructs river flows and irrigation systems, 38,39 thus increasing flood risk and hindering navigation 40 and recreational water activities.…”
Section: Introductionmentioning
confidence: 99%